Complete mitochondrial genome of Agapornis lilianae (Psittaciformes: Psittacidae), with its phylogenetic analysis. Issue 2 (3rd July 2019) - Chen, Yun-Xia; Zhou, Yong-Wu; Hou, Sen-Lin; Huang, Ya-Lin
Abstract: In this paper, we reported the complete mitogenome of Agapornis lilianae . A. lilianae mitogenome is 16, 720bp base pairs long. The overall base compositions of complete mitogenomes of A. lilianae is 29.66% A, 21.5% T, 34.59% C, 14.25% G. All genes exhibit the typical mitochondrial gene arrangement and transcribing directions. The phylogenetic analysis based on 21 mitochondrial sequence data suggested that A. lilianae are closely related to the same genus specie Agapornis roseicollis . The results obtained here would be useful for the conservation and phylogeny of A. lilianae .